Implementasi Sistem Port Knocking Dalam Meningkatkan Keamanan Mikrotik Di PIT PT CDE COAL Bengkulu Utara - Ramadhan, Suwandi; Abdullah, Dedy; Darmi, Yulia; Khairullah, Khairullah (Institut Bakti Nusantara, 2024)
In the modern technological era, the development of computers and networks has presented various new challenges, particularly in terms of security. The Internet of Things (IoT) and next-generation network technologies such as 5G have transformed the way we interact with devices and networks, bringing significant security risks. Therefore, PT Cakrawala Dinamika Energi (PT CDE) faces similar issues at its mining site. Network security in this area remains vulnerable to attacks by unauthorized parties. This research aims to enhance network security at PT CDE by using a port knocking system on MikroTik. The port knocking method adds a layer of security by only allowing access after a correct sequence of 'knocks' on specific ports has been performed. Implementation was carried out by adding special firewall rules on MikroTik to manage login ports and address lists. The system's success was tested through several login attempts by both authorized admins and intruders who did not follow the correct port sequence. The research results show that the implementation of the port knocking system successfully increased the security of MikroTik at the PT CDE mining site. All login attempts by intruders, using various different device IPs, were blocked. Conversely, authorized admin logins were successful after following the correct port knocking sequence. With these results, it is hoped that network security in the mining area can be further assured, providing a foundation for further development in network security management.